Analysis of the Role of Serambi Indonesia Media in Improving Political Education in the 2019 Legislative Elections in Bireuen District, Aceh - Chaidir Ali (Jurnal Politik Indonesia, 2023)
The role of the Serambi Indonesia media is urgently needed to have a positive effect on increasing political education for the public as voters in general elections because the media has a strong influence in shaping one's cognition, where the media provides information and knowledge that ultimately shapes perceptions, and perceptions will influence attitudes and behavior. The Serambi Indonesia media was chosen because the media contains a lot of political news and can keep up with the times. Serambi Indonesia is one of the largest print media spread across Aceh Province. This study aims to find out the role of the Serambi Indonesia media in increasing political education among the public in the 2019 legislative elections in the Bireuen Regency. This study uses a qualitative method. Qualitative research focuses on collecting data that is descriptive and analytical on the Serambi Indonesia website, intending to uncover more specific phenomena that can provide a more in-depth picture of Indonesian Serambi media in improving political education in the 2019 legislative elections in the Biereuen Regency. With that, Serambi Indonesia provides information or political news published by Serambi Indonesia which is very important and very influential. the reader in receiving the message conveyed.